1993
DOI: 10.1111/j.1467-9280.1993.tb00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Foreign Language Vocabulary and the Spacing Effect

Abstract: In a 9-year longitudinal investigation, 4 subjects learned and relearned 300 English-foreign language word pairs. Either 13 or 26 relearning sessions were administered at intervals of 14, 28, or 56 days. Retention was tested for 1.2.3. or 5 years after training terminated. The longer intersession intervals slowed down acquisition slightly, but this disadvantage during training was offset by substantially higher retention. Thirteen retraining sessions spaced at 56 days yielded retention comparable to 26 session… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
216
1
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(237 citation statements)
references
References 18 publications
16
216
1
4
Order By: Relevance
“…However, the beneficial effect of distributed practice has also been found in primary school children learning pictures (e.g., Toppino & DiGeorge, 1984;Toppino, Kasserman, & Mracek, 1991), words (e.g., Toppino & DeMesquita, 1984), or a combination of pictures and words (e.g., Cahill & Toppino, 1993;Rea & Modigliani, 1987;Toppino, 1993). Moreover, some studies have demonstrated that distributed practice enhances foreign vocabulary learning in undergraduate students (e.g., Bahrick, Bahrick, Bahrick, & Bahrick, 1993;Bloom & Shuell, 1981).…”
mentioning
confidence: 99%
“…However, the beneficial effect of distributed practice has also been found in primary school children learning pictures (e.g., Toppino & DiGeorge, 1984;Toppino, Kasserman, & Mracek, 1991), words (e.g., Toppino & DeMesquita, 1984), or a combination of pictures and words (e.g., Cahill & Toppino, 1993;Rea & Modigliani, 1987;Toppino, 1993). Moreover, some studies have demonstrated that distributed practice enhances foreign vocabulary learning in undergraduate students (e.g., Bahrick, Bahrick, Bahrick, & Bahrick, 1993;Bloom & Shuell, 1981).…”
mentioning
confidence: 99%
“…The number of ten vocabulary tests used to collect subjects" data (excluding the standard-setting pre-test ("Test 0")) was chosen arbitrarily to maximize the potential possible within the confines of a single semester, a limitation stemming from the quasi-experimental setting. Had it been possible to extend the study, treatment sessions organized on an optimal spacing basis may also have resulted in more reliable data; studies have shown such a schedule to be advantageous for learning and long-term retention of a variety of materials, including L2 vocabulary (Baddeley, 1997;Bahrick, Bahrick, Bahrick & Bahrick, 1993;Hulstijn, 2001;Mizuno, 1996Mizuno, , 2003. Moreover, as the mean receptive score of 74.58% on the pre-test ("Test 0") indicates, the subjects had an initially high receptive knowledge of the material, a factor that limited the usefulness of the analysis applied in response to the research question and sub-question.…”
Section: Resultsmentioning
confidence: 99%
“…The connection between the context signal and new piece of information is initially very fragile; however, remaining activated for only two to thirty seconds, after which time it is subject to decay if not reactivated by an additional stimulus or thought process (Cowan, 2000). One of the simpler ways to achieve this reactivation is through repetition of the material, a method that has enjoyed widespread and longstanding support from both within and without SLA literature (Bahrick, Bahrick, Bahrick & Bahrick, 1993;Cowan, 2000;Ellis & Beaton, 1993;Ellis, 2002;Ericsson & Kintsch, 1994;Gass & Mackey, 2002;Gupta & MacWhinney, 1997;Henriksen, 1999;Hulstijn, 2002;Knowles, 2008;Lewis, 1993;Mohensi-Far, 2008a, 2008bNakata, 2008;Nation, 2001Nation, , 2002Papagno & Vallar, 1992;Schmitt, 2000;Segler, 2002;Tarone, 2002;Wei, 2007;Weil, 2008). In addition to strengthening the specific relationship between the new piece of information and its context signal, such repetition also helps to secure the context signal into the wider neural network (Henriksen, 1999).…”
Section: From Working Memory To Long-term Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption is based on the Retention Curve for Recall Vocabulary by Bahrick (1984) or Bahrick et al (1993), respectively, which was included in the framework of a life-span analysis. In this context 773 persons were interviewed whose participation in language courses dated back differently long.…”
Section: Development Of the Indexmentioning
confidence: 99%